Evaluation of dose of ovaprim for inducing ovarian maturation and ovulatory response in the catfish, Heteropneustes fossilis - Singh, D V; Ram, R N; Singh, I J (Indian Journal of Fisheries, 2011)
The present study was aimed to standardise the economically effective dose ofovaprim (OPm) which could induce oocyte development, growth, maturationand ovulation within optimum period in Heteropneustes fossilis. Mature femalesweighing 50Â±5 g of 15Â±2 cm in length were injected with variable doses of OPm(0.10, 0.15 or 0.20 ml/fish) during 2nd week of July and ovulation was checkedat 8, 16, 20 and 24 h interval. The ovarian hydration was significantly highafter 20 h at 0.10 and 0.15 ml dose levels and 8 h at 0.20 ml dose. In OPminjected fish, spawning was 65% at 24 h, 25% at 20 h and 75% at 16 h in 0.10,0.15 and 0.20 ml dose levels, respectively. The ovulated eggs diameter was significantlymore in the 0.20 ml OPm injected group compared to the other two.The number of ovulated eggs/fish was also significantly more in 0.20 ml OPminjected fish in comparison of 0.15 ml but the difference was insignificant with0.10 ml OPm injected group. The histological observations revealed that ovariesof the control fish contained large number of yolky oocytes usually passingthrough various atretic stages. The follicular cells were not active and even theprocess of intravesicular yolk synthesis in vitellogenic oocytes was not marked.In all OPm injected groups, dose and duration dependent development, growthand maturation of oocytes were superior at higher dose which included proliferationof primordial cells forming oogonial cyst, differentiation of follicularlayer into active thecal and granulosa cells, induction of intra and intervesicularyolk synthesis and incorporation, advancement of maturational events in fullygrown oocytes i.e. germinal vesicle movement and germinal vesicle breakdown,separation of follicular wall and ovulation. Above observations suggested that0.20 ml/fish dose of OPm was most effective in inducing oocyte growth andmaturation, however, 0.10 ml/fish of OPm on the basis of spawning responsewas though slightly delayed in comparison of 0.20 ml, which might be consideredas economically appropriate dose for inducing ovulation and spawning inthis species.